Discriminating factors excluding patients from a catheter-based left atrial appendage closure and an outcome analysis of non-intervened and intervened patients - Fastner, Christian; Jabbour, Claude; Behnes, Michael; Sartorius, Benjamin; Wenke, Annika; El-Battrawy, Ibrahim; Ansari, Uzair; Borggrefe, Martin; Akın, Ibrahim (Archives of medical science, 2024)
Introduction: The catheter-based left atrial appendage closure (LAAC) has evolved as an alternative to oral anticoagulation (OAC) among non-valvular atrial fibrillation (AF) patients in whom long-term OAC is contraindicated. In daily practice, however, a sizeable number of patients who have...